Grokking deep learning in motion (Manning Publications, 2019)
"Grokking Deep Learning in Motion is a new course that takes you on a journey into the world of deep learning. Rather than just learn how to use a single library or framework, you'll actually discover how to build these algorithms completely from scratch! Machine learning has made remarkable progress in recent years. Deep-learning systems now enable previously impossible smart applications, revolutionizing image recognition and natural-language processing, and identifying complex patterns in data. To really get the most out of deep learning, you need to understand it inside and out, but where do you start? This course is the perfect jumping off point!"--Resource description page